Mechanism of death after early decompressive craniectomy in traumatic brain injury. (July 2018) - Zeiler, FA; Trickey, K; Hornby, L; Shemie, SD; Lo, BWY; Teitelbaum, J
Background: Decompressive craniectomy in devastating traumatic brain injury is controversial. The impact of decompressive craniectomy on mechanism of death is unclear in the literature to date. Our goal was to determine the mechanism of death between those receiving early decompressive craniectomy and those managed medically. Methods: We performed an institutional retrospective review, from June 2003 to June 2013, of adult patients with devastating blunt traumatic brain injury undergoing early decompressive craniectomy who subsequently died. We compared this group to a retrospectively matched group based on: age, pre-hospital KPS, Marshall diffuse computed tomography grades, Injury Severity Scores, and admission laboratory values. Results: Forty patients were analyzed; 20 with decompressive craniectomy and 20 without. The two groups were similar based on admission demographics, with the only statistically significant difference being platelet levels. Upon analysis, through both univariate and multivariate regression analysis, the mechanism of death was significantly different (p = 0.003; OR: 0.07 (0.01–0.41) and p = 0.04; OR: 0.08 (0.01–0.87)) with the decompressive craniectomy and non-decompressive craniectomy groups displaying neurological death rates of 10.0% versus 60.0%, respectively, with all other patients in both groups dying secondary to circulatory arrest after withdrawal of life-sustaining therapy. Time to death was significantly longer in the decompressive craniectomy group (2.83 vs. 9.21 days, respectively) (p = 0.01; OR: 0.65 (0.46–0.91). Conclusions: Progression to neurological death appears to be more common in those devastating blunt traumatic brain injury patients treated medically compared to those undergoing early decompressive craniectomy. Given the implications of end-of-life care and societal implications, the mechanism of death determination and organ donation should be reported as relevant outcomes in devastating traumatic brain injury studies.